Ethnopharmacological survey among migrants living in the Southeast Atlantic Forest of Diadema, São Paulo, Brazil - Rodrigues Eliana; Domingues Marcus; Garcia Daniel (BMC, 2010)
Abstract Background Understanding how people of diverse cultural backgrounds have traditionally used plants and animals as medicinal substances during displacements is one of the most important objectives of ethnopharmacological studies. An ethnopharmacological survey conducted among migrants living in the Southeast Atlantic Forest remnants (Diadema, São Paulo, Brazil) is presented herein. Methods Ethnographical methods were used to select and interview the migrants, and botanical and zoological techniques were employed to collect the indicated resources. Results We interviewed five migrants who described knowledge on 12 animals and 85 plants. Only 78 plants were present in Diadema, they belong to 37 taxonomic families; 68 were used exclusively for medicinal purposes, whereas 10 were reported to be toxic and/or presented some restriction of use. These taxa were grouped into 12 therapeutic categories (e.g., gastrointestinal disturbances, inflammatory processes or respiratory problems) based on the 41 individual complaints cited by the migrants. While the twelve animal species were used by the migrants to treat nine complaints; these were divided into six categories, the largest of which related to respiratory problems. None of the animal species and only 57 of the 78 plant species analysed in the present study were previously reported in the pharmacological literature; the popular knowledge concurred with academic findings for 30 of the plants. The seven plants [Impatiens hawkeri W. Bull., Artemisia canphorata Vill., Equisetum arvensis L., Senna pendula (Humb. & Bonpl. ex Willd.) H.S. Irwin & Barneby, Zea mays L., Fevillea passiflora Vell. and Croton fuscescens Spreng)] and the two animals (Atta sexdens and Periplaneta americana) that showed maintenance of use among migrants during their displacement in Brazilian territory, have not been studied by pharmacologists yet. Conclusions Thus, they should be highlighted and focused in further pharmacology and phytochemical studies, since the persistence of their uses can be indicative of bioactive potentials.